Crystallographic analysis of ground- and space-grown thermostable T1 lipase crystal - Mohamad Aris, Sayangku Nor Ariati (2013)
X-ray crystallography is a major tool to provide three dimensional structures. High resolution protein crystal data is important in revealing a highly accurate structure at atomic level. This is essential in order to understand the properties and function of the protein. In crystallization process, convection and sedimentation is thought to be detrimental for growth of high quality protein crystals. Both aspects can be avoided by either working in gelled systems, working in systems of small dimensions, or in the absence of gravity. In this research, crystallization by using counter diffusion method in space was performed with the aim to obtain high resolution diffracting crystals with better internal order to improve the accuracy of the structure. Recombinant T1 Lipase from Geobacillus zalihae was successfully purified to homogeneity via two step affinity chromatography followed by ion exchange chromatography with 8.9 % yield. Purified T1 lipase was then crystallized in microbatch and vapour diffusion methods. The best crystal growth was obtained in Formulation 21 (Crystal Screen 2) with optimum growth temperature of 20 °C. The crystallization set up condition was applied to counter diffusion method for space experiment as well as ground control. Crystallization of T1 lipase under microgravity condition experiment was done in collaboration with JAXA (Japanese Aerospace Exploration Agency) under the JAXA-UPM Protein Crystal Growth (PCG) #2 Flight 2 program. The synchrotron diffraction data set were collected to 1.3 Å and 1.1 Å resolutions and belonged to monoclinic C2 Space group for ground grown and space grown crystal, respectively. The major difference between the two crystal growth systems is the lack of convection and sedimentation in microgravity environment resulted in the growth of much higher quality crystals of T1 lipase. The structural analysis of T1 lipase was performed using molecular replacement method with final R factor 0.134 (Rfree 0.162) for ground-grown crystal and 0.129 (Rfree 0.150) for space-grown crystal,respectively. The structure of T1 lipase crystal contains two molecules per asymmetric unit with 387 amino acids each. Overall topology showed of α/β hydrolase fold containing catalytic triad active site and covered by α-helix 6 and α-helix 7 as a ‘lid’. The structure contained zinc and calcium binding site which was important for the structural stabilization. Comparative crystallographic analysis revealed that the space-grown crystal structure has improved as compared to ground grown crystal. This study has shown that crystallization in counter diffusion method using microgravity environment improved the internal order of crystals thus gave a more precise three dimensional structure.